Death, 'deathlessness' and existenz in Karl Jaspers' philosophy - Peach, Filiz (Edinburgh University Press, 2008)
Filiz Peach provides a clear explanation of Jaspers philosophy of existence clarifying and reassessing the concept of death that is central to his thought
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Jaspers, Karl / 1883-1969; Jaspers, Karl -- 1883-1969; Existentialism; Death; Philosophie; Tod